Background-free Detection of Mouse Antibodies on Mouse Tissue by Anti-isotype Secondary Antibodies. (August 2021) - Mascadri, Francesco; Ciccimarra, Roberta; Bolognesi, Maddalena M.; Stellari, Fabio; Ravanetti, Francesca; Cattoretti, Giorgio
Immunodetection on mouse routinely processed tissue via antibodies raised in mice faces cross-reactivity of the secondary anti-mouse reagents with endogenous immunoglobulins, which permeate the tissue. Various solutions to this problem have been devised and include endogenous Ig block with anti-mouse Fab fragments or directly conjugated primary antibodies. Mouse isotype-specific antibodies, differently from reagents directed against both heavy and light chains, fail to detect endogenous Ig after fixation and embedding, while providing a clean and specific detection system for mouse antibodies on mouse routinely processed tissue.